Fixed/Predefined-time synchronization of memristor-based complex-valued BAM neural networks for image protection - Liu, Aidi; Zhao, Hui; Wang, Qingjie; Niu, Sijie; Gao, Xizhan; Su, Zhen; Li, Lixiang (Frontiers in Neurorobotics, 2022)
This paper investigates the fixed-time synchronization and the predefined-time synchronization of memristive complex-valued bidirectional associative memory neural networks (MCVBAMNNs) with leakage time-varying delay. Firstly, the proposed neural networks are regarded as two dynamic real-valued systems. By designing a suitable feedback controller, combined with Lyapunov method and inequality technology, a more accurate upper bound of stability time estimation is given. Then, a predefined-time stability theorem is proposed, which can easily establish a direct relationship between tuning gain and system stability time. Any predefined time can be set as controller parameters to ensure that the synchronization error converges within the predefined time. Finally, the developed chaotic MCVBAMNNs and predefined-time synchronization technology are applied to image encryption and decryption. The correctness of the theory and the security of the cryptosystem are verified by numerical simulation.